A Literary Review of Artavakshaya in Ayurveda w.s.r. to Oligo Hypomenorrhea - Review Based on Literary Study - Sangeeta; Meena, Narendra Kumar; khathuria, Diksha (International Research Journal of Ayurveda & Yoga, 2022)
In Ayurveda classics, all Gynaecological problems are described in Yonivyapada and Artava Vikara . Due to changed lifestyle, the physical and emotional stress increases. This leads to many physiological changes that ends with the disruption of ‘H-P-O’ axis and may leads to various gynaecological disorders. Artavakshaya is one of amongst them. Ratio of Menstrual disorder is raising in gynaecological practice which is a precursor of infertility and other problems. Artavakshaya is also seen as one of the manifestation of the Yonivyapadas like Arajaska/Lohitkshaya Yonivyapada & Vatala Yonivyapada, along with ksheen artavadusti and jataharini. Modern science & Ayurveda both offer treatment for the Artavakshay, but in modern science very little options are there like hormonal therapy while Ayurveda describes various modalities like life style modification, correction of diet ,oral medication and Panchakarma procedures so this study is undertaken to through the light on classical reference of Artavakshaya with modern correlation & its Ayurvedic management.